2023
DOI: 10.3390/vaccines11030610
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Worry in the Kurdistan Region of Iraq during the Mpox (Monkeypox) Outbreak in 2022: An Online Cross-Sectional Study

Abstract: The rapid spread of monkeypox (mpox) has been declared as a public health emergency of international concern (PHEIC). The present study aimed to assess the knowledge, attitude, and worry levels of the general population in the Kurdistan region of Iraq regarding the ongoing mpox multi-country outbreak. An online cross-sectional survey was conducted between 27–30 July 2022, using a convenience sampling method. The questionnaire was adapted from previous studies addressing the same topic. The independent Student’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 47 publications
3
26
0
Order By: Relevance
“…Other studies have also reported differences in vaccination intent depending on the place of residence. Ahmed et al [39] revealed that there were signi cant differences in knowledge and acceptance in the Kurdistan region of Iraq. Kurdistan is divided into four regions: Sulaymaniyah, Erbil, Duhok, and Halabja, where Sulaymaniyah demonstrated the highest level of knowledge, positive attitude, and concern towards mpox.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also reported differences in vaccination intent depending on the place of residence. Ahmed et al [39] revealed that there were signi cant differences in knowledge and acceptance in the Kurdistan region of Iraq. Kurdistan is divided into four regions: Sulaymaniyah, Erbil, Duhok, and Halabja, where Sulaymaniyah demonstrated the highest level of knowledge, positive attitude, and concern towards mpox.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the data by continent, the following vaccination intention prevalences were found: In Asian countries, it was 64% (95% CI: 53-74%; 13883 participants; 17 studies; I 2 = 99%) (17, 18, 20, 22, 24-27, 29, 34, 35, 37, 39-42, 44); in African countries, it was 43% (95% CI: 39-47%; 1538 participants; 3 studies; I 2 = 53%) (19,23,28); in European countries, it was 62% (95% CI: 45-78%; 35811 participants; 6 studies; I 2 = 99%) (21, 30-32, 36, 38); and in American countries, it was 63% (95% CI: 32-89%; 1426 participants; 3 studies; I 2 = 99%) (16, 33, 43) (Figure S2). Furthermore, when focusing on the target population of the studies, the following vaccination intention prevalences against Mpox were observed: among the general population, it was 54% (95% CI: 45-62%; 10296 participants; 11 studies; I 2 = 99%) (18, 19,22,23,25,26,29,[39][40][41]43); among healthcare workers, it was 57% (95% CI: 33-79%; 3333 participants; 10 studies; I 2 = 99%) (17,24,28,30,33,35,37,38,42,44); and among the LGBTI community, it was 76% (95% CI: 70-82%;39029 participants; 8 studies; I 2 = 98%) (16, 20,21,27,31,32,34,36) (Figure S4).…”
Section: Prevalence Of Intention To Vaccinate Against Monkeypoxmentioning
confidence: 93%
“…An epidemic of mpox was labeled a Public Health Emergency of International Concern by the WHO on July 23, 2022. 3 , 26 , 27 , 62 , 63 Even though evidence is just starting to emerge, it is possible that mpox can present with more severe symptoms in immunocompromised adults than in the general population. 64 , 65 The CDC found that among 57 patients hospitalized with severe mpox infection between August and October 2022, 90% had underlying immunocompromising diseases, including 31 people with HIV who had a CD4 cell count of fewer than 50 cells/mm.…”
Section: The Ongoing 2022 Mpox Outbreakmentioning
confidence: 99%